Simulation of electromechanical valve drive on single cylinder four stroke free piston diesel engine - Fyroz Ziffa, Mohd Mustafa Kamal (2008)
In conventional internal combustion engines, the camshaft is an apparatus often used in piston engines to operate the valves. The camshaft is connected to the crankshaft. The relationship between the rotation of the camshaft and the rotation of the crankshaft is of critically importance. Since the valves control the flow of air and fuel mixture intake and exhaust gases, they must be opened and closed at the appropriate time during the stroke of the piston. In the free piston engine, there is no crankshaft. So, the electromechanical valve drive (EMVD) will take the part in make the valve moving as usual. In this project, the model of EMVD will be developed in 3D CAD software.